Drug addiction and its Effect on the Pregnant Mother and her Fetus (The International Journal for Scientific Research, 2024)
Drug addiction is considered one of the threats that threaten the stability of societies due to the many problems it results from. Psychological, physical, social and economic problems are among the fundamental reasons for the spread of drug addiction in the social environment, and their abuse leads to multiple crises that disintegrate family and social ties in general. It is known that the foundation of societies and their progress is the human element. It represents that a pregnant woman who is addicted to narcotic drugs is exposed to the risk of premature birth and as a result of the effect of the drug, she does not Be aware of the early signs and symptoms of labor.Drug addiction is one of the serious psychological and social problems that many individuals are exposed to. It affects individuals’ physical and psychological health and their moral and economic affairs, which negatively affects all the details of their lives. Women’s addiction to drugs is anti-social behavior that expresses a decline in social values ​​and a defect in the performance of institutions. Socialization of their role. There are many harmful effects surrounding a pregnant woman who is addicted to drugs, as these harms are not limited to the health of the pregnant woman only, but extend to the fetus and society as a whole. Despite all the negative effects that occur as a result of addiction, we find a large percentage of women who continue to use drugs. In the face of this worrying situation that heralds the arrival of a generation of addicts. Through this research, we will address the effects of a woman’s drug addiction on her health and the health of the fetus, and its social, economic, and security harms.
Keywords: Drug Addiction; Pregnant Mother; Fetus Abortion